2014
DOI: 10.1007/s13277-014-2947-0
|View full text |Cite
|
Sign up to set email alerts
|

Leishmanial sphingolipid induces apoptosis in Sarcoma 180 cancer cells through regulation of tumour growth via angiogenic switchover

Abstract: Sphingolipids are membrane and intracellular lipids that typically modulate cellular processes to cause cell death. Exogenous administration of sphingolipids may cause restriction of tumour growth and several alternative strategies are being used to control the cell growth. The microbes, their cellular component(s) or metabolites like DHA, EPA and also FTY720 have been employed as new therapeutic entities to regulate the disease condition. The therapeutic efficacy of lipids from Leishmania donovani in rheumato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Further studies have shown that DHA can alleviate cerebral ischemia/reperfusion injury, maintain blood-brain barrier integrity, and reduce blood-brain barrier permeability [5]. Das S et al reported that DHA can inhibit the expression of VEGF and its receptor, Flk-1, through the VEGF pathway, thereby significantly inhibiting corneal neovascularization and tumor vascular growth [12]. On the other hand, eicosapentaenoic acid could effectively reduce the level of Ang-2 in the plasma of chronic diabetic patients [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies have shown that DHA can alleviate cerebral ischemia/reperfusion injury, maintain blood-brain barrier integrity, and reduce blood-brain barrier permeability [5]. Das S et al reported that DHA can inhibit the expression of VEGF and its receptor, Flk-1, through the VEGF pathway, thereby significantly inhibiting corneal neovascularization and tumor vascular growth [12]. On the other hand, eicosapentaenoic acid could effectively reduce the level of Ang-2 in the plasma of chronic diabetic patients [39].…”
Section: Discussionmentioning
confidence: 99%
“…DHA may be a promising drug for the treatment of cerebral ischemia/reperfusion injury [11]. Studies have reported that DHA can inhibit the expression of VEGF and its receptor, Flk-1, through the VEGF pathway to significantly inhibit the growth of corneal neovascularization and tumor blood vessels [12]. Recent studies have shown that DHA reduced apoptosis in rat brain microvascular endothelial cells induced by an underlying oxygen and glucose deprivation environment, thus decreasing Ang-2 and VEGF synthesis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Sphingomyelin, a lipid found in cell membranes and intracellular regions, plays a crucial role in regulating cellular processes such as proliferation, differentiation, and apoptosis ( Maceyka and Spiegel, 2014 ). After treating Sarcoma 180 cells with Leishmania sphingomyelin in vitro , reactive oxygen species production and caspase activation were regulated, resulting in up-regulation of pro-apoptotic molecules (Bad, Bax and P53) and down-regulation of anti-apoptotic molecules (Bcl-2 and PARP) ( Das et al., 2015b ). This treatment also inhibited the production of pro-angiogenic factors such as VEGF, CD34, and Ang-2, affecting the cell division cycle and thus impacting tumor growth ( Das et al., 2015a ).…”
Section: Other Types Of Protozoamentioning
confidence: 99%
“…Regarding melanoma destruction by apoptosis is an unique feature of Leishmania sphingolipids as there is no convenient way destined to eliminate these skin cancer cells. Intracutaneous injection starting from a very small dose, one can attempt to treat melanoma through apoptosis induction [24,25].…”
Section: Leishmanial Promastigote Sphingolipids Apoptosis and Cancermentioning
confidence: 99%